House of God or House of David. - Eslinger, Lyle M., 1953- (Journal for the study of the Old Testament. Supplement series ;, 1994)
2 Samuel 7 has always been a focal point in discussion about the Davidic covenant and its relationship to the exodus (or Sinai) covenant. This new rhetorical study of the speeches of Yahweh and David in 2 Samuel 7 examines the dynamics of the conversation between the two characters, a conversation essentially about houses and obligation. The reading proposes that talk of a Davidic dynasty is a diversionary strategy that Yahweh uses to deflect David''s interest from a temple building project. It also suggests that the manner in which Yahweh presents the offer of dynasty conceals an empty offer.